Optimal Imaging of In Vitro Clot Sonothrombolysis by MR‐Guided Focused Ultrasound. Issue 2 (14th November 2011) - Durst, Christopher; Monteith, Stephen; Sheehan, Jason; Moldovan, Krisztina; Snell, John; Eames, Matt; Huerta, Thomas; Walker, William; Viola, Francesco; Kassell, Neal; Wintermark, Max
<x xml:space="preserve">Abstract</x> ABSTRACT BACKGROUND AND PURPOSE As magnetic resonance‐guided focused ultrasound (MRgFUS) sonothrombolysis relies on mechanical rather than thermal mechanisms to achieve clot lysis, thermometry is not useful for the intraoperative monitoring of clot breakdown by MRgFUS. Therefore, the purpose of this study was to evaluate the optimum imaging sequence for sonothrombolysis. METHODS In vitro blood drawn from 6 healthy volunteers was imaged using T1, T2 spin‐echo, and T2 gradient‐echo (GRE) sequences both before and after sonication using an Insightec ExAblate 4000 FUS transducer. Signal intensities of the three MR imaging sequences were measured and normalized to background signal for each time point. Representative samples of the pre‐ and postsonication clot were also sent to pathology for hematologic analysis. RESULTS After sonication, the clot in the treatment tube was fully lysed as evidenced by physical and hematologic evaluation. The difference between pre‐ and postsonicated normalized signal intensity ratios demonstrated statistical significance only on T2 and GRE sequences (P < .001). However, significant blooming artifact limited interpretation on all GRE images. CONCLUSION T2 is the most appropriate sequence for the evaluation of mechanical MRgFUS sonothrombolysis of an in vitro clot. These findings are consistent across the oxidative states of clot up to 48 hours.